IMPLEMENTATION OF THE USE OF PHET SIMULATION TO FACILLITATE STUDENTS’ PHYSICS LEARNING ON WAVE MATERIAL - Wylla Agustiningrum (Universitas Negeri Surabaya, 2026)
Physics with various concepts that are still difficult to understand, requires a learning media that can explain the concept more easy and interesting. The limitations of real media are an obstacle in implementing virtual learning, so teachers need digital media as an alternative, one of which is PhET Simulation. This study aims to explore the use of PhET Simulation in facilitating students' physics learning on wave material. This study uses a qualitative approach with a descriptive method. The results obtained state that PhET Simulation can improve students' understanding of concepts, experimental skills, and cognitive learning outcomes. Thus, the implementation of PhET Simulation in learning physics on wave material is very useful for significantly improving the understanding of physics concepts because this simulation connects abstract concepts with real phenomena that are difficult to observe directly, trains students' science process skills, and this simulation can make physics learning on wave material more effective, fun, and can be accessed at any time without the limitations of physical practicum tools.